PENGARUH KEPEMIMPINAN, KEPERCAYAAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Bangun Sugito, Untung Sriwidodo & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2007)
ABSTRACT Research into this by taking sample all employees PD BPR Bank Pasar Surakarta amounting to 40 people Target of this research to study and analyze leadership influence, trust, and job satisfaction on employees performance at PD BPR Bank Pasar Surakarta by partial and together. Result of this research show the existence of influence is significant between independent variable with dependent variable by partial and also together. Variable owning biggest influence is job satisfaction. Job satisfaction of employees can be formed to through: activity which mentally challenge, proper reward, job condition supporting, friend job according to, according to personality with job. Keywords: leadership influence, trust, job satisfaction, employees performance